Pedagogical Practices in the Technology Intervened Indian Education System (Indian Journal of Social Science and Literature (IJSSL), 2024)
Globally, the advent of technology has caused significant changes to the education system, and India is not an exception. The incorporation of technology into education has created new opportunities for teaching and learning, as well as the opportunity to improve pedagogical practices. This paper aims to investigate the pedagogical practices in the Indian education environment influenced by technology. The study is conducted by conducting a systematic literature review of research articles published in various journals and conference proceedings over the past decade. The review focuses on the pedagogical practices in technology-enhanced education in India, such as multimedia resources, collaborative learning, gamification, and personalized learning. In addition, the paper discusses the obstacles and constraints educators encounter in implementing these practices and suggests potential solutions to overcome them. According to the study, incorporating technology into education can enhance the quality of teaching and learning in India. Nevertheless, it is essential to implement pedagogical practices that are applicable and effective in the Indian context. The paper recommends that educators receive the necessary training and resources to implement these practices effectively. The study concludes that technology-enhanced education has enormous potential to trans- form the education system in India and create more equitable and accessible learning opportunities for all students.